Hepaticites iporangae Ricardi-Branco, Faria, Jasper, and Guerra-Sommer, 2011 from the early Permian of the Paraná Basin, Brazil, is not a liverwort but a tracheophyte. (12th August 2016) - Uhl, Dieter; Jasper, André; Valerius, Talyssa; Manfroi, Joseline; Guerra-Sommer, Margot; Ricardi-Branco, Fresia Soledad
Abstract: From new and more complete material, which includes frond fragments with casts of tracheid remains of the rachis, it can be demonstrated that the putative liverwort Hepaticites iporangae Ricardi-Branco, Faria, Jasper, and Guerra-Sommer, 2011, from the early Permian Rio Bonito Formation (Sakmarian) of the Paraná Basin, Brazil, is not a bryophyte but a tracheophyte. The new material was collected from the same locality and layer as the type material, in the Quitéria outcrop in the municipality of Encruzilhada do Sul, state of Rio Grande do Sul, Brazil. From the morphology of the deeply dissected pinnatifid pinnules with narrow laminar lobes, the taxon is provisionally reassigned to the genus Rhodeopteridium . Thus we propose the new combination ' Rhodeopteridium ' iporangae new combination for this taxon. This new systematic interpretation contributes to our understanding of early liverworts (by removing Hepaticites iporangae as a possible taxon thereof) and clarifies an issue of diversity of the flora of the early Permian Rio Bonito Formation resulting from the original misidentification.